Fingolimod Nanoemulsions at Different Particle Sizes Define the Fate of Spinal Cord Injury Recovery. (16th August 2022) - Poormoghadam, Delaram; Shiadeh, Bita Rasoulian; Azedi, Fereshte; Tavakol, Hani; Rezayat, Seyed Mahdi; Tavakol, Shima
Abstract : Spinal cord injury (SCI) is a debilitating condition for which no definitive treatment has yet been identified. Notably, it influences other tissues through inflammatory reactions and metabolic disturbances. Therefore, fingolimod (FTY-720), as an FDA-approved inflammatory modulator, would be promising. In the present study, nanocarriers with two distinct monodisperse particle sizes of 60 (nF60) and 190 (nF190) nm were prepared via low-(stirring) and high-energy (probe ultrasound) emulsion oil in water (O/W) methods. Larger nanocarriers showed higher EE% and sustained-release profile than smaller nanocarriers. Neural stem cell (NSC) viability and lactate dehydrogenase (LDH) release were studied in the presence of nanocarriers and free FTY-720. The results indicated that nanocarriers and free FTY-720 enhanced NSC viability compared with the control group. However, nF190 induced significantly less cell membrane damage than nF60. Nanocarriers and free FTY-720 enhanced motor neuron recovery in SCI rats, while body weight and return to bladder reflux by nF190 were significantly higher than those in the nF60 group. Return to bladder reflux might be due to the role of FTY-720 in the regulation of detrusor muscle tone and preservation of the integrity of vessels by acting on endothelial cells. Moreover, nF190 gained higher soleus muscle weight than the free drugs; probably decreasing proinflammatory cytokines in the soleus diminishes muscular atrophy in SCI rats. In summary, it might be said that larger nanocarriers with sustained-release profile and less cell membrane damage seem to be more efficient than smaller ones to manage SCI and enhance bladder reflux. These data will help pharmaceutical companies select the correct particle size for nanodrugs and develop more efficient drug formulations to treat SCI.